Crystal structure of 3-{5-[3-(4-fluorophenyl)-1- isopropyl-1H-indol-2-yl]-1H-pyrazol-1-yl}indolin-2- one ethanol monosolvate - Rahman, Md. Lutfor; Kulkarni, Ajaykumar D.; Mohd. Yusoff, Mashitah; Huey, Chong Kwong; Ching, Kheng Quah (International Union of Crystallography, 2016)
The title indolin-2-one compound, C28H23FN4OC2H6O, crystallizes as a 1:1 ethanol solvate. The ethanol molecule is disordered over two positions with refined site occupancies of 0.560 (14) and 0.440 (14). The pyrazole ring makes dihedral angles of 84.16 (10) and 85.33 (9) with the indolin-2-one and indole rings, respectively, whereas the dihedral angle between indolin-2-one and indole rings is 57.30 (7). In the crystal, the components are linked by N—H O and O—H O hydrogen bonds, forming an inversion molecule–solvate 2:2 dimer with R4 4(12) ring motifs. The crystal structure is consolidated by – interaction between pairs of inversion-related indolin-2-one rings [interplanar spacing = 3.599 (2) A ° ].